2016
DOI: 10.1177/1066896916632588
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CD-105 as an Angiogenic Modulator in Odontogenic Myxomas and Dental Follicles

Abstract: Aim Odontogenic myxoma is a benign intraosseous neoplasm of the jaws, with a locally aggressive behavior and a high recurrence rate. CD-105 is a homodimeric cell membrane glycoprotein and is a component of the TGF-β1 growth factor receptor complex that modulates angiogenesis by regulating the proliferation, differentiation and cellular migration. The aim of this study is to quantify the microvascular density of the odontogenic myxoma based on the expression of CD-105. Materials and Methods The analysis include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…3a,b). This situa-tion may be explained by the fact that CD-105 expression, contrary to CD34, is a characteristic property of newly formed blood vessels and not of previously-existing blood and lymphatic vessels (34). CD 105 in POT was found mainly in blood vessels located in the areas of greater condensation of mesenchymal cells, particularly in the subepithelial region, thus signaling neoangio-genesis activity in this tumoral area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3a,b). This situa-tion may be explained by the fact that CD-105 expression, contrary to CD34, is a characteristic property of newly formed blood vessels and not of previously-existing blood and lymphatic vessels (34). CD 105 in POT was found mainly in blood vessels located in the areas of greater condensation of mesenchymal cells, particularly in the subepithelial region, thus signaling neoangio-genesis activity in this tumoral area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies performed by our group ( 14 , 28 , 29 ) have shown that the growth of the odontogenic myxoma is the product of a complex multifactorial process in which cell proliferation and angiogenesis are involved mainly in the early stages. With the present results, we suggest that the growth of these neoplasms can also be related with the production and performance of different mechanisms related with the RANK / RANK-L / OPG system.…”
Section: Discussionmentioning
confidence: 99%